The history of education at the confluence of other disciplines: foundations, areas of investigation and issues.: The Swiss Journal of Educational Research (2000-2019), a mirror of international issues? - Hofstetter, Rita (Swiss Journal of Educational Research, 2021)
What are the foundations, areas of investigation and issues in the history of education? A longitudinal analysis of all the articles on the history of education in the Swiss Journal of Educational Research since 2000 provides answers to these questions and demonstrates the astonishing vitality of this discipline. We examine the profiles and trajectories of the authors of the articles in the history of education, problematizing in the background the status of the discipline at the crossroads of other social sciences. In a second part, we analyse and discuss the historical issues dealt with in the journal, divided into 4 categories, in the light of major historiographic trends and mirroring international issues. We open with some reflections on possible perspectives.